2023
DOI: 10.1177/03057356231165327
|View full text |Cite
|
Sign up to set email alerts
|

Groove as a multidimensional participatory experience

Abstract: Groove is a popular and widely used concept in the field of music. Yet, its precise definition remains elusive. Upon closer inspection, groove appears to be used as an umbrella term with various connotations depending on the musical era, the musical context, and the individual using the term. Our aim in this article was to explore different definitions and connotations of the term groove so as to reach a more detailed understanding of it. Consequently, in an online survey, 88 participants provided free-text de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 78 publications
1
4
0
Order By: Relevance
“…While our results confirm past qualitative findings that groove is deeply tied to rhythmic features, 2,56,57 the typical coupling to pleasure was only observed within the context of common 4/4 meters. This dissociation between pleasure and the urge to move may have arisen because pleasure is more multifaceted, being affected by other properties of music like melodic complexity, 58,59 harmonic complexity, 60 and timbre.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…While our results confirm past qualitative findings that groove is deeply tied to rhythmic features, 2,56,57 the typical coupling to pleasure was only observed within the context of common 4/4 meters. This dissociation between pleasure and the urge to move may have arisen because pleasure is more multifaceted, being affected by other properties of music like melodic complexity, 58,59 harmonic complexity, 60 and timbre.…”
Section: Discussionsupporting
confidence: 90%
“…Vocals were excluded because they capture attention more than other instruments, 62,79 are often highly syncopated, 80 could induce unwanted gender effects, [81][82][83] are subject to great individual differences in musical taste, [84][85][86] and because lyrical content impacts emotions and the urge to move. 56,87 The Pulse Entropy of each clip was calculated using the MIR Toolbox's mirpulseclarity function with the 'EntropyAutocor' setting as in previous work. 4,5,7,8,20,27,29,[88][89][90] The meter of each clip was assessed and labeled by a professional musicologist (author GSC); 34 were in 4/4 (Common) meter and 29 were in meters outside of 4/4 (Uncommon).…”
Section: Musical Clipsmentioning
confidence: 99%
“…However, he and others also recognized that experiencing stimulating rhythmic music is also associated with pleasure (Madison, 2006;Todd, 2000). Groove is a complex, multi-faceted concept (Duman et al, 2021(Duman et al, , 2023Stupacher et al, 2022b) that can differ in definition from one individual to another (Hosken, 2020). Most authorities now agree that groove is two-dimensional and can be described as the motivational quality (or qualities) of music that evokes a combination of pleasure and wanting to move (Janata et al, 2012, Levitin et al, 2018, and Mathews et al, 2019.…”
Section: Groove and Groove Musicmentioning
confidence: 99%
“…However, empirical support for a relationship between groove and catchiness has been sparse and often merely insinuated. For example, in a recent study in which participants reported their own definitions of groove, ‘catchy’ came up several times [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…In many studies, the groove experience has been equaled to PLUMM, but some accounts have shown a more nuanced picture [4,5], added a social dimension [6], or described it as a state of being [7]. Duman et al [8] developed a comprehensive definition: "Groove is a participatory experience (related to immersion, movement, positive affect, and social connection) resulting from the subtle interaction of specific music-(such as time-and pitch-related features), performance-, and/or individual-related factors" (p. 19). In the present text, we use PLUMM when referring specifically to the pleasure and urge to move aspects of groove, and groove when the concept goes beyond PLUMM, such as the experience as a whole or research on groove in general.…”
Section: Introductionmentioning
confidence: 99%